Characterization of a Novel Protease Inhibitor from the Edible Mushroom Agaricus bisporus - Vishvakarma, Reena; Mishra, Abha (Protein and Peptide Letters, 2022)
Background: Protease inhibitors inhibit the activity of protease enzymes; hence, they are essentially involved in the regulation of the metabolic processes involving protease enzymes and the protection of the host organism against external damage due to proteases. These inhibitors are abundantly present in all living organisms but have not been much reported in mushrooms. Mushrooms are one of the major food components of humans, with delicious taste and high nutritional value. Mushrooms also have therapeutic and economic significance. The edible mushrooms with medicinal properties are much in commercial demand. To date, the presence of protease inhibitors has not been reported much in edible mushrooms. The present study reports the characterization of a protease inhibitor isolated from the common white button mushroom Agaricus bisporus. Objective: The objective of the present study is to characterize the novel protease inhibitor from Agaricus bisporus in order to determine its nature and activity under varying environmental conditions. Methods: The protease inhibitor was characterized through SDS PAGE, gel filtration chromatography, and de novo sequencing in order to determine its molecular mass and sequence, respectively. The optimum pH, temperature, and thermal stability were studied to determine the optimum working range of the protease inhibitor. The protease inhibitory activity (%) was determined in the presence of metal ions, surfactants, oxidizing agents, and reducing agents. The kinetic parameters and the type of inhibition exhibited by the protease inhibitor were determined using casein and trypsin protease enzyme. Results: The protease inhibitor was found to be a low molecular mass compound of 25 kDa. The de novo sequencing matched the inhibitor against a 227 amino acid containing peptide molecular mass of 24.6 kDa molecular mass. The protease inhibitory activity (%) was found highest at pH 7.0 and temperature 50 °C, and the inhibitor was stable from pH 4.0-9.0 and temperature 30-80 °C. In the presence of metal ions, the residual protease inhibitory activity (%) enhanced in the presence of Na+, Mg2+, and Fe3+. The residual activity increased in the presence of the surfactant SDS slightly in comparison to control, while it decreased in the case of Triton-X and Tween 20. The presence of oxidizing agents, hydrogen peroxide and dimethyl sulfoxide decreased the residual inhibitory activity. The protease inhibitor’s activity was unaffected by the reducing agents, dithiothreitol and β-mercaptoethanol, at up to 2mM concentration, but it decreased at higher concentrations. The inhibitor exhibited uncompetitive inhibition against trypsin with an inhibitory constant of 166 nM, indicating a strong affinity towards the protease, with a half-life of 93.90 minutes at 37 °C. Conclusion: Protease inhibitors isolated from mushrooms are generally small in size, more stable, and tolerant towards varying external conditions. The protease inhibitor isolated from Agaricus bisporus also exhibited similar characteristics.
Keywords: characterization